Effect of Low-Intensity High-Repetition Versus High-Intensity Low-Repetition Elastic Band Resistance Training on Functional Physical Fitness and Myokine Levels in Older Adults - Moon Jin Lee; Jun-Young Sung; Jiyoun Kim (Applied Sciences)
This study investigates the effects of low-intensity high-repetition (LI-HR) and high-intensity low-repetition (HI-LR) resistance training (RT) on functional fitness and myokines in older adults. A total of 30 participants (mean age ~76 years) were randomized into control (n = 10), LI-HR (n = 10), or HI-LR (n = 10) groups. Participants in LI-HR and HI-LR groups performed elastic band-based RT three times per week for 12 weeks. Pre- and post-intervention assessments included functional fitness (relative grip strength, sit-to-stand, 4 m walk, timed up-and-go (TUG)), ankle muscle strength, lower extremity power, and myokine levels (IL-6, IGF-1, SPARC, BDNF). Both experimental groups showed significant IL-6 reduction (LI-HR: p = 0.033; HI-LR: p = 0.015) and IGF-1 increase (LI-HR: p = 0.003; HI-LR: p < 0.001). SPARC increased significantly only in the HI-LR group (p = 0.021). Functional improvements were noted in TUG for both groups, while the 4 m walk improved significantly in the HI-LR group (p < 0.001). Body fat percentage increased in both LI-HR (p = 0.003) and HI-LR (p = 0.047). In conclusion, both LI-HR and HI-LR RT effectively enhance functional fitness and key myokines, with LI-HR emerging as a promising, accessible option for older adults.